Long term oncologic surveillance in Maffucci syndrome: A case report - Michael E. McGarry (Journal of Oncological Sciences, 2017)
Maffucci syndrome is a rare disorder of bone and soft tissue characterized by multiple enchondromas and hemangiomas. Patients with this disorder are at significantly increased risk for malignant transformation of the lesions; of particular note are chondrosarcomas, gliomas, ovarian tumors and other sarcomas. Additionally, patients are affected by skeletal malformations including limb length discrepancies and deformities of the hands, feet and upper and lower limbs. Because of the rarity of the condition, there is currently no consensus for long-term screening of these patients. We suggest a regimen including annual surveillance using advanced imaging and routine physical examination.